PENYULUHAN STRATEGI KELUARGA DALAM MENGHADAPI DAMPAK COVID-19 DI LINGKUNGAN DESA BERGAS LOR TAHUN 2020 - dhias fajar widya permana, dhias (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2021)
Indonesia, even in the world, is currently experiencing a COVID-19 pandemic, which is a deadly virus. Many people have been infected and died. Therefore, we as a society must be aware of this situation by adopting a healthy lifestyle. The purpose of this service is to obtain results that can be used as references and relevant results for consideration and input. Counseling on family strategies in dealing with COVID-19 will give the community a goal of the importance of family strategies when dealing with the COVID-19 pandemic. So that in a pandemic situation like this month, a lot of family strategies are needed in dealing with these times in order to stay in good health and be able to be creatively active to add and save part of the community's income in the pandemic era. The method in this service will use survey methods, question and answer and provide counseling through both online via the internet, persuasive enhancements by prioritizing health protocols and by listening to public complaints both in terms of health and psychology. The results of this method will be given input and counseling to get the strategy, then these results will be described in the form of a description that can be used as a reference by the community. In a healthy condition, people can work well and can be creative to increase their appetite in this pandemic era, by exercising a lot, and choosing healthy foods and minimizing problems both with family and society that often occur. The outputs in this service will contribute to the knowledge and references needed by the community as initial knowledge in community strategies during a pandemic at times like this. So that it will add to the repertoire of knowledge, especially in the world of health. And can not be separated from physical fitness and sports that are part of health